2016
DOI: 10.3892/mmr.2016.5820
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Pyropia yezoensis glycoprotein on chronic ethanol consumption-induced hepatotoxicity in rats

Abstract: The present study investigated the protective effect of Pyropia yezoensis glycoprotein (PYGP) against chronic ethanol consumption‑mediated hepatotoxicity in rats. Male Sprague-Dawley rats (n=20; 6 weeks old) were randomly divided into four groups. The rats in each group were treated for 30 days with the following: i) CON group, distilled water only; ii) EtOH group, 20% ethanol 3.7 g/kg/BW; iii) EtOH+150 group, 20% ethanol 3.7 g/kg/BW+PYGP 150 mg/kg/BW; iv) EtOH+300 group, 20% ethanol 3.7 g/kg/BW+PYGP 300 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…It serves as a fairly specific indicator of liver status (16) . The decrease in serum GPT values found in our study is consistent with those reported in other investigations with hepatoprotective medicinal plants (17,18) , especially the fact that pretreatment with the extract may be effective in reducing serum GPT before drinking alcohol (17) . The hepatotoxic action of ethanol in control group is evident, since the absorbed ethanol performs its biotransformation process mainly in the liver, at a rate of 10 mL hour (19) ; its metabolism is mainly carried out by the enzymes alcohol dehydrogenase (ADH), aldehyde dehydrogenase (ALDH) and cytochrome P450 (CYP2E1) (20) .…”
Section: Resultssupporting
confidence: 92%
“…It serves as a fairly specific indicator of liver status (16) . The decrease in serum GPT values found in our study is consistent with those reported in other investigations with hepatoprotective medicinal plants (17,18) , especially the fact that pretreatment with the extract may be effective in reducing serum GPT before drinking alcohol (17) . The hepatotoxic action of ethanol in control group is evident, since the absorbed ethanol performs its biotransformation process mainly in the liver, at a rate of 10 mL hour (19) ; its metabolism is mainly carried out by the enzymes alcohol dehydrogenase (ADH), aldehyde dehydrogenase (ALDH) and cytochrome P450 (CYP2E1) (20) .…”
Section: Resultssupporting
confidence: 92%
“…Anti-cancer polysaccharides (dietary fiber, porphyran), phospholipids, sterol, peptide [17,[46][47][48][49][50][51][52][53][54] Prevention of cardiovascular disease (e.g., hypertension, atherosclerosis, ischemia) betaine, dietary fiber, taurine, porphyran [17,[55][56][57][58][59][60][61] Antioxidant effect (e.g., Anti-ageing) porphyran, glycoprotein, polyphenols, tocopherols, peptide [62][63][64][65][66][67] Anti-inflammatory effect and immunomodulation glycoprotein, porphyran [64,[68][69][70][71][72][73] Alcohol metabolism glycoprotein [74,75] Prevention of nervous diseases (e.g., Alzheimer's diseases, methylmalonic acidemias) taurine, porphyran [38,76,77] Prevention of bone disease (e.g., osteoporosis, rheumatoid arthritis) porphyran, glycoprotein [64,78] Anti-diabetes mellitus phenolic compounds (carotenoids, anthocyanins), polysaccharides (porphyran), peptide [79][80][81][82] Porphyran is the distinctive dietary fiber found in laver, and its health effects were intensively studied to determine the nutritional/functional quality of ...…”
Section: Health Functionality Major Components Linked To Health Functmentioning
confidence: 99%
“…Moreover, it exerts various physiological effects, including anti-tumorigenic [22], anti-inflammatory [23], anti-photoaging [24], and anti-oxidant effects [25]. Previous studies reported that glycoproteins derived from P. yezoensis help reduce inflammatory stress induced by lipopolysaccharides in RAW264.7 cells and hepatotoxicity induced by ethanol in a rat model [23,26]. Moreover, P. yezoensis glycoproteins prevented cytotoxicity induced by D-galactosamine in Hepa 1c1c7 cells and acetaminophen-induced liver injury in a rat model [27,28].…”
Section: Introductionmentioning
confidence: 99%